Retreatment for hepatitis C virus direct‐acting antiviral therapy virological failure in primary and tertiary settings: The REACH‐C cohort. Issue 8 (28th May 2022) - Carson, Joanne M.; Hajarizadeh, Behzad; Hanson, Josh; O'Beirne, James; Iser, David; Read, Phillip; Balcomb, Anne; Davies, Jane; Doyle, Joseph S.; Yee, Jasmine; Martinello, Marianne; Marks, Philippa; et al.
Abstract: Virological failure occurs in a small proportion of people treated for hepatitis C virus (HCV) with direct‐acting antiviral (DAA) therapies. This study assessed retreatment for virological failure in a large real‐world cohort. REACH‐C is an Australian observational study ( n = 10, 843) evaluating treatment outcomes of sequential DAA initiations across 33 health services between March 2016 to June 2019. Virological failure retreatment data were collected until October 2020. Of 408 people with virological failure (81% male; median age 53; 38% cirrhosis; 56% genotype 3), 213 (54%) were retreated once; 15 were retreated twice. A range of genotype specific and pangenotypic DAAs were used to retreat virological failure in primary ( n = 56) and tertiary ( n = 157) settings. Following sofosbuvir/velpatasvir/voxilaprevir availability in 2019, the proportion retreated in primary care increased from 21% to 40% and median time to retreatment initiation declined from 294 to 152 days. Per protocol (PP) sustained virological response (SVR12) was similar for people retreated in primary and tertiary settings (80% vs 81%; p = 1.000). In regression analysis, sofosbuvir/velpatasvir/voxilaprevir (vs. other regimens) significantly decreased likelihood of second virological failure (PP SVR12 88% vs. 77%; adjusted odds ratio [AOR] 0.29; 95%CI 0.11–0.81); cirrhosis increased likelihood (PP SVR12 69% vs. 91%; AOR 4.26; 95%CI 1.64–11.09). Indigenous Australians had lower likelihood of retreatment initiation (AOR 0.36; 95%CI 0.15–0.81). Treatment setting and prescriber type were not associated with retreatment initiation or outcome. Virological failure can be effectively retreated in primary care. Expanded access to simplified retreatment regimens through decentralized models may increase retreatment uptake and reduce HCV‐related mortality.